CRIME AND JUSTICE IN THE ERA OF MASS MEDIA - Abdul Ghaffar Korai; Imtiaz Ahmed Memon; Ahad Ghaffar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study was undertaken to find crime and justice in the era of mass media. The mass media framework can cover a wide scope of residents and administrators, which likewise makes it a significant asset for the criminal justice framework and all going with legal and police associations. It is coordinated by three interrelated subjects, which have been the primary focal point of studies: the content, results, and reasons for crime explanations in the mass media. The mass Medias market model proposes that mass medias associations decide the substance to be covered and the substance delivered by the mass medias dependent on the financial benefit created by the offer of mass medias items.